Graves′ Disease With Pretibial Myxoedema - Sood Apra; Sood Ajay; Souza Paschal D; Pandhi R K (Wolters Kluwer Medknow Publications, 1998)
A 45 year old man presented with asymptomatic skin coloured nodules, erythmatous plaques on both legs along with features of thyrotoxicosis. Investigations confirmed the diagnosis of Gravesâ€ disease with pretibial mayxoedema. The patient became euthyroid with carbimazole and the skin lesions responded partially to antithyoroid treatment and local corticosteroids.